Elements of a non-gaussian analysis on the spaces of functions of infinitely many variables - Kachanovskii, N. A. (Ukrains’kyi Matematychnyi Zhurnal, 2010)
We present a review of some results of the non-Gaussian analysis in the biorthogonal approach and consider elements of the analysis associated with the generalized Meixner measure. The main objects of our interest are stochastic integrals, operators of stochastic differentiation, elements of theWick calculus, and related topics.